Biblioteka szkolna a przygotowanie uczniów do samokształcenia w świetle aktów legislacyjnych z lat 1945-1982 - Antczak , Mariola (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The realization of a new form of education – an interdisciplinary path reading and media education – began in 1999 when for the first time this expression was used, according to the Ministry of Education (MEN) directive about basis of education programme. However, the advent of the path, which comprised such issues as a book, a library, scientific information or media, was not only the result of activities at the end of 1990s. Therefore it would be inadequate to assume 1999 as the beginning of education of a given period and so other facts which contributed to its appearance have to be mentioned. Many years before, librarian circles had taken initiatives owing to which legal acts concerning libraries and qualification requirements of school librarians were changed. This, on the other hand, had an impact on librarians’ involvement in pupils’ preparation for self-education. After the WW II there were no separate rooms which could function as libraries and the modest collection of books constituted one or two bookshelves either in a corridor or in a classroom. Therefore there was no poin in creating a post for a librarian and so one of the teachers – a teacher of Polish language, a teacher of history or another one – was responsible for lending books. In the Decree from 1946 it is mentioned that the library personnel should be well prepared to work with books and readers, though no details referring to librarians’ qualifications were stated. Although the library was recognized as an institution whose aim was to prepare teachers and pupils for self-education, didactic activity of librarians in the form of separate lessons was out of question. The librarian was simply seen as a person lending books. The article focuses on the analysis of legislative acts, which described the role of school librarians in education. The analysis already began in 1945, which was briefly justified above. The year 1982 was assumed as the upper time limit – and it was after this year when Work programme of a school library came into force – a document which imposed an obligation on librarians to conduct lessons as part of reading and information preparation. The years to come, starting from 1983, mark a new stage in the history of school library science.